Microperimetry in Optic Neuritis - Indrish Bhatia; Shveta Lukhmana; Digvijay Singh; Vimala Menon; Pradeep Sharma; Rohit Saxena (The Ophthalmology, 2016)
Aim: To evaluate microperimetry as a tool for visual field assessment in optic neuritis and compare it with standard automated perimetry. Methods: A case-control study was conducted at a tertiary eye care centre in India. Ten cases of unilateral optic neuritis and 10 healthy controls underwent a detailed ophthalmic evaluation and visual field testing at presentation and 1 month and 3 months follow-up. Visual fields were charted using both the standard automated perimeter (10-2 and 30-2 programs) and microperimeter (central 20 degree program) at each visit. Results: The visual acuity at presentation of the affected eye, fellow eye and control eyes was 0.27±0.19, 0.93±0.14 and 0.94±0.17 respectively. The affected eye visual acuity improved significantly to 0.89±0.24 (p<0.001) at the 3 months follow-up visit. The mean sensitivity thresholds of 10-2 visual field test at presentation were 14.16±11.51, 30.40±1.98 and 31.04±1.95 respectively of which the affected eye showed a significant improvement over 3 months to 28.90±8.36 (p<0.001). The mean sensitivity thresholds of 30-2 visual field test at presentation were 12.88±10.32, 26.03±2.59 and 27.99±2.31 respectively of which the affected eye and fellow eye showed a significant improvement over 3 months to 26.02±7.54 (p<0.001) and 27.86±1.77 (p<0.03) respectively. The mean sensitivity thresholds of microperimetry 20 degree visual fields at presentation were 5.60±7.32, 16.54±1.46 and 17.30±1.64 respectively of which the affected eye showed a significant improvement over 3 months to 16.41±4.87 (p<0.001). Microperimetry fields did not improve completely at 1 month unlike the 10-2 fields and correlated strongly with visual recovery. The 30-2 fields were the most sensitive to determine subclinical affliction of the fellow eyes in optic neuritis. Conclusion: Microperimetry is a sensitive test to evaluate visual fields in optic neuritis and corresponds with visual recovery. The larger 30 degree module is still indispensible for visual field assessment in optic neuritis.